2009
DOI: 10.1080/00048670902817679
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Psychoanalytic Psychotherapy for Adolescents with Serious Mental Illness: 12 Month Naturalistic Follow-Up Study

Abstract: This naturally occurring sample of seriously ill adolescents referred to Child and Adolescent Mental Health Services for assessment were suffering complex mental illness and poor mental health. Empirical evidence is presented that psychoanalytic psychotherapy is an effective addition to Child and Adolescent Mental Health Services treatment as usual for mental illness in adolescence, particularly for more severe and complex cases. The naturalistic study design and participant attrition are possible study limita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Where age groups have been directly compared, younger children appear to benefit more than older ones, with the likelihood of improvement during treatment declining with age (Target and Fonagy 1994b;Deakin and Nunes, 2009;Odhammar et al, in press). However, there are also studies that suggest that older children and adolescents can also benefit from psychodynamic therapy (Baruch 1995, Baruch et al, 1998Sinha and Kapur 1999;Tishby et al, 2007;Chanen et al, 2008;Tonge et al, 2009;Lock et al, 2010). .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where age groups have been directly compared, younger children appear to benefit more than older ones, with the likelihood of improvement during treatment declining with age (Target and Fonagy 1994b;Deakin and Nunes, 2009;Odhammar et al, in press). However, there are also studies that suggest that older children and adolescents can also benefit from psychodynamic therapy (Baruch 1995, Baruch et al, 1998Sinha and Kapur 1999;Tishby et al, 2007;Chanen et al, 2008;Tonge et al, 2009;Lock et al, 2010). .…”
Section: Discussionmentioning
confidence: 99%
“…In another recent study, Tonge et al (2009) report on the effectiveness of psychoanalytic psychotherapy for adolescents with serious mental illness, based on a naturalistic longitudinal study. Forty adolescents aged 12 to 18 years, with a range of 'severe mental illnesses', were offered psychoanalytic psychotherapy once or twice weekly, whilst 40 were offered treatment as usual (TAU).…”
Section: Findings Of the Review: Outcomes For Children And Young Peopmentioning
confidence: 99%
“…A naturalistic longitudinal study 83 A series of reports of the Tavistock Study of children in the care system [84][85][86][87] provided a systematic investigation of PP for children in care. The study aimed to assess whether these severely deprived children could benefit from psychotherapy.…”
Section: Comparison With Taumentioning
confidence: 99%
“…In a naturalistic study of Baruch and Fearon (2002), which involved 151 teenagers and young adults, the retention was much higher among those patients who had internalizing symptoms. Tonge, Pullen, Hughes, and Beaufoy (2009) also compared psychodynamic psychotherapy with treatment as usual (TAU) in a longitudinal study on 55 teenagers. The results showed that the largest effect was evident in those who suffered from the most severe symptoms when seeking therapy.…”
mentioning
confidence: 99%